Unraveling the Tapestry of the Ottoman Empire (KULT_online, 2024)
Losing Istanbul: Arab-Ottoman Imperialists and the End of Empire by Mostafa Minawi presents a comprehensive reassessment of the decline of the Ottoman Empire, with a particular focus on the agency of Arab-Ottoman imperialists. The study challenges established historiographical narratives and emphasized the proactive engagement of Arab-Ottoman actors in shaping historical trajectories.